Effectiveness of maintenance electroconvulsive therapy—Evidence from modifications due to the COVID‐19 pandemic. (18th May 2021) - Methfessel, Isabel; Besse, Matthias; Belz, Michael; Zilles‐Wegner, David
Abstract: Objective: Continuation and maintenance ECT (c‐/m‐ECT) are effective in the prevention of relapse and recurrence of both affective and psychotic disorders. However, data are scarce concerning the trajectories of severe mental disorders after the end of c‐/m‐ECT. This prospective study investigates the clinical outcome of patients with versus without modifications of their c‐/m‐ECT schedules. Methods: In the context of the COVID‐19 pandemic, ECT capacities were restricted at many clinics in early 2020. All patients receiving c‐/m‐ECT in March and April 2020 at our department ( n  = 53, unipolar depression, bipolar disorder, schizophrenia) were followed up for six months to investigate the impact of treatment modifications imposed by the pandemic. Based on individual decisions, c‐/m‐ECT was either (a) continued without modification, (b) continued with reduced frequency, or (c) discontinued. Results: Both reduced frequency and discontinuation of c‐/m‐ECT were associated with significant clinical deterioration as measured by CGI‐I (Clinical Global Impression Scale ‐ Global Improvement) during the six‐month follow‐up when compared to the subgroup of patients without any treatment modification ( p  = 0.005, p  = 0.011). Furthermore, patients with discontinued or reduced c‐/m‐ECT showed significantly higher rates of rehospitalizations ( p  = 0.028) and new acute courses of ECT ( p  = 0.018). Conclusion: Despite the limitations of a heterogeneous and relatively small sample, our study strongly corroborates the effectiveness of c‐/m‐ECT in a real‐world population. Especially, patients with shorter time since index ECT seem to be at high risk for severe clinical deterioration in the case of treatment discontinuation or reduction.